Community Psychology Perspective on Ecological Issues: Based on Psychological Intervention - Mehrad, Aida (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The purpose of the current literature review is to clarify the important role of community psychology regarding ecological issues and illustrated its critical function based on psychological intervention. The results of this investigation explained that community psychology as one of the essential fields of psychology, has substantial involvement on ecological issues and it can examine these issues based on psychological intervention. In truth, these ecological issues that some of them explained in this study (child maltreatment, drug addiction, school dropping out, and teen pregnancy) have been examined based on the psychological aspect for finding best solution way from the side of expert psychologists and counselors. Consequently, this research focused on teenagers that face with community issue via different ways, and should be considered by parents, schools, society, and government in every community and country; otherwise, it will appear any inconvenient behaviors and reactions amongst teenagers.